Rationale for and design of the TRUE‐AHF trial: the effects of ularitide on the short‐term clinical course and long‐term mortality of patients with acute heart failure. (13th November 2016) - Packer, Milton; Holcomb, Richard; Abraham, William T.; Anker, Stefan; Dickstein, Kenneth; Filippatos, Gerasimos; Krum, Henry; Maggioni, Aldo P.; McMurray, John J.V.; Mebazaa, Alexandre; O'Connor, Christopher; Peacock, Frank; et al.
Abstract: The TRUE‐AHF is a randomized, double‐blind, parallel‐group, placebo‐controlled trial which is evaluating the effects of a 48‐h infusion of ularitide (15 ng/kg/min) on the short‐ and long‐term clinical course of patients with acute heart failure. Noteworthy features of the study include the early enrolment of patients following their initial clinical presentation (within 12 h), and entry blood pressure criteria and thresholds for the adjustment of drug infusion rates, which aim to minimize the risk of hypotension. The trial has two primary endpoints: (i) cardiovascular mortality during long‐term follow‐up; and (ii) the clinical course of patients during their index hospitalization. Cardiovascular mortality is evaluated in this event‐driven trial by following all randomized patients for the occurrence of death until the end of the entire study without truncation at an arbitrarily determined early time point. The clinical course during the index hospitalization is evaluated using the hierarchical clinical composite endpoint, which combines information regarding changes in symptoms and the occurrence of in‐hospital worsening heart failure events and death into a single ranked metric that captures interval clinical events and minimizes the likelihood of missing data and confounding due to intensification of background therapy. The design of the TRUE‐AHF trial capitalizes on lessons learned from earlier trials and aims to evaluate definitively the potential benefit of ularitide in patients with acute heart failure. Trial registration: NCT01661634